2015
DOI: 10.1177/1045389x15577657
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the super-strong behavior of magnetorheological fluid in simultaneous squeeze-shear with the Péclet number

Abstract: Under squeezing flow, magnetorheological fluid can undergo a strengthening phenomenon which results in a drastic increase of its yield stress. This behavior, also known as the super-strong effect, could be used to significantly increase the performance (e.g. torque-to-weight) of rotary magnetorheological fluid devices (e.g. brakes, clutches), but has yet to be exploited due to limited predictability of the phenomenon. To better understand the occurrence of the super-strong effect, a novel test bench capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The strengthening effect has been theoretically explained using the local field theory by Zhang et al [12], and more recently interpreted in terms of the Péclet number [13] In a recent study, Ruiz-López et al [14] developed a micromechanical model to explain the rheological properties of MR fluids under slow compression. They found that the yield compressive stress depends linearly on the particle volume fraction and on the magnetic field strength squared: 𝜏 𝑌𝐶 ~𝜙𝐻 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening effect has been theoretically explained using the local field theory by Zhang et al [12], and more recently interpreted in terms of the Péclet number [13] In a recent study, Ruiz-López et al [14] developed a micromechanical model to explain the rheological properties of MR fluids under slow compression. They found that the yield compressive stress depends linearly on the particle volume fraction and on the magnetic field strength squared: 𝜏 𝑌𝐶 ~𝜙𝐻 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The producer datasheet reports a yield stress around 50 kPa when the magnetic field is above 300 KA/m. Although it is not specified in the producer TDS we can find some information in literature work [8][9][10][11][12][13][14][15][16][17] about the average dimension of the spherical MR particles, which is around 20µm, with a density around 2950-3150 kg/m 3 . The settling and the agglomeration of the particles is prevented thanks to proprietary surfactants and additives.…”
Section: Methodsmentioning
confidence: 99%
“…The changes in the magnetic field are due to the fluid gap modification and due to the different phase volume of the system, as expected for hard particles. A similar approach was used in other works about the so called squeeze-strengthen effect [8][9][10][11][12][13][14][15][16][17] in which many researchers demonstrates that there is a strong enhancement of the apparent yield stress of the fluid when there is a combination of shear and compression. This behaviour is due to the formation of larger particles columns, as stated by [11,18] thanks to the compressive state resulting in a higher yield stress when the magnetic field is applied.…”
Section: Introductionmentioning
confidence: 96%
“…This relationship is not directly proportional due to the MRF having a complex behavior, according to Ref. [14]. Parameter x 1 and x 2 are the displacements of the slave and master pistons, respectively.…”
Section: Description Of the Analytical Model 251 Two-degree-of-freedo...mentioning
confidence: 99%